Instagram Story as Learning Media in a Form of German Vocabulary Quiz for 10th Grade Students at SMAN 5 Malang - Ajeng Vantika; Edy Hidayat (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This research aims to describe the use of Instagram Story as German learning media in a form of vocabulary quiz and the responses of students to the use of the media. The research method is descriptive qualitative and there were 19 students as the data source. The data were collected by conducting an observation and questionnaires. As a result of observation, students were enthusiast on taking the vocabulary quiz at Instagram Story because Instagram has become a part of their daily routine. This shows that Instagram Story could be implemented as German learning media since students are familiar to it. Based on the questionnaires result, the students’ responses were positive. The use of Instagram Story as vocabulary quiz has enriched students’ knowledge of German vocabularies especially about Kennenlernen topic. In addition, it motivated them to explore German vocabularies. Moreover, learning German with Instagram Story is attractive for the students.